2022
DOI: 10.18203/2349-3291.ijcp20222414
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported tinnitus in pediatric age group: our experiences at a tertiary care teaching hospital in eastern India

Abstract: Background: Many children do not complain of tinnitus spontaneously. Tinnitus in the pediatric age group is an overlooked symptom. It has not received much attention in the pediatric age group than adult age. Children rarely complain spontaneously of tinnitus but present it when questioned. Objective of the study was to assess tinnitus in the pediatric age group with or without hearing impairment and its severity.Methods: This is a cross-sectional study on the children in the age group of 5 to 18 years who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hearing loss as a risk factor for tinnitus in children has been demonstrated in some studies, however. In a cross-sectional study on children aged 5–18 years who attended a tertiary care teaching hospital in Eastern India with a primary complaint of hearing impairment, Swain and Baliarsingh [ 2 ] examined the relationship between pure tone audiometry (up to 8 kHz) and tinnitus (assessed by questionnaire). Of the 172 children enrolled in the study, 104 self-reported tinnitus, of whom 67 (64.4%) were subsequently diagnosed with hearing loss.…”
Section: Prevalence Risk Factors and Pathophysiology Of Tinnitus In C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing loss as a risk factor for tinnitus in children has been demonstrated in some studies, however. In a cross-sectional study on children aged 5–18 years who attended a tertiary care teaching hospital in Eastern India with a primary complaint of hearing impairment, Swain and Baliarsingh [ 2 ] examined the relationship between pure tone audiometry (up to 8 kHz) and tinnitus (assessed by questionnaire). Of the 172 children enrolled in the study, 104 self-reported tinnitus, of whom 67 (64.4%) were subsequently diagnosed with hearing loss.…”
Section: Prevalence Risk Factors and Pathophysiology Of Tinnitus In C...mentioning
confidence: 99%
“…The review also concluded that problems relating to the impact of tinnitus on quality of life and feelings of isolation are important problem domains to consider when managing a child who has tinnitus. Swain and Baliarsingh [ 2 ] also suggest tinnitus can have a negative effect on social interactions and learning in children.…”
Section: Investigation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation